Product authenticity versus globalisation—The Tulsi case - Jürges, Gabriele; Sahi, Vaidurya; Rios Rodriguez, Daniela; Reich, Eike; Bhamra, Sukvinder; Howard, Caroline; Slater, Adrian; Nick, Peter (PLOS ONE, 2018)
Using the Indian medicinal plant Tulsi (Holy Basil) as a case study, we have tested to what extent the discrepancy between vernacular and scientific nomenclature can be resolved, whether the presumed chemical diversity underlying the medicinal use of Tulsi has a genetic component, and whether it is possible to detect this genetic component using genetic barcoding markers. Based on four plastidic markers, we can define several haplotypes within Ocimum that are consistent across these markers. Haplotype II is congruent with O. tenuiflorum, while haplotype I extends over several members of the genus and cannot be resolved into genetically separate subclades. The vernacular subdivision of Tulsi into three types (Rama, Krishna, Vana) can only be partially linked with genetic differences–whereby Rama and Krishna Tulsi can be assigned to O. tenuiflorum, while Vana Tulsi belongs to haplotype I. This genetic difference is mirrored by differences in the profiles of secondary compounds. While developmental state and light quality modulate the amplitude to which the chemical profile is expressed, the profile itself seems to be linked with genetic differences. We finally develop an authentication assay that makes use of a characteristic single nucleotide polymorphism in one of the barcoding markers, establishing a differential restriction pattern that can be used to discriminate Vana Tulsi.